Diagnostic capability of fine‐needle aspiration cytology in assessment of intraosseous lesions of the jaws: A systematic review. Issue 5 (17th January 2020) - Pilati, Sarah F. M.; dos Santos, Natália; Melo, Gilberto; Mello, Fernanda W.; Rivero, Elena R. C.
Abstract: Purpose: To systematically review (SR) and critically appraise studies that investigated the diagnostic capability of fine‐needle aspiration cytology (FNAC) in the assessment of intraosseous lesions of the jaws. Methods: Six main electronic databases and three gray literature databases were searched aiming diagnostic studies, which were selected in a two‐phase process. Risk of bias (RoB) of included studies was assessed using the Revised Tool for the Quality Assessment of Diagnostic Accuracy Studies. Results: A total of eight articles were included, of which six evaluated the FNAC smear technique exclusively, one assessed both smear and cell‐block techniques, while one investigated only the cell‐block technique. With regard to the FNAC smear technique, from 134 benign lesions investigated, concordance with the histopathological diagnosis was achieved in 64.17% of cases. In addition, considering the 32 malignant lesions assessed through this technique, concordance with histopathology was achieved in all cases. Regarding the cell‐block technique, only benign lesions (n = 40) were evaluated in the included studies, in which the concordance rate with histopathology was of 77.5%. The overall RoB judgment was "at risk of bias" for seven included studies mostly due to lack of information or reportedly absence of blinding of evaluator. Conclusions: Within the limitations of this SR, FNAC presented modest to satisfactory diagnostic capability for the assessment of intraosseous jaw lesions, showing concordance rates higher than 64% for the smear and 77% for the cell‐block technique. Also, considerably high concordance rates were found for the assessment of malignant lesions regarding FNAC smear technique.